Literature Review: Evaluasi Model Edukasi HIV/AIDS di Posyandu Remaja - Andina Vita Sutanto; Zubaida Rohmawati; Edwin Daru Anggara (Yayasan Literasi Sains Indonesia, 2025)
HIV/AIDS infection remains a public health challenge among Indonesian adolescents despite extensive educational efforts. This study presents a structured literature review (systematic review) following PRISMA guidelines to evaluate the effectiveness of HIV/AIDS education models in Youth Integrated Health Posts (Posyandu Remaja) from 2015 to 2025. Searches in Google Scholar identified four primary studies meeting inclusion criteria: two quantitative pre-post interventions with cadres and youth, one qualitative study, and one community service project. Findings indicate that interventions employing lectures, group discussions, informational leaflets, educational videos, and peer education enhanced adolescent knowledge scores by an average of 75 % and reduced the proportion of low-knowledge participants from 84% to zero after a brief session. Participatory approaches and collaboration with religious leaders and community institutions were key facilitators. Nevertheless, social stigma, limited cadre capacity, short program duration, and insufficient counseling facilities undermined long-term impact on actual behavior change, such as HIV testing uptake and consistent condom use. Consequently, this review recommends developing a comprehensive education module encompassing reproductive rights, sexual orientation diversity, the U = U concept, and psychosocial support; advanced cadre training; cross-sector integration; and digital technology utilization to ensure program sustainability and effectiveness.